NextGen approach to hydrological forecasting: Adapting PyCPT tool for hydrological forecasting - Minoungou, Bernard; Ali, Abdou; Houngnibo, Mandela C.; Mohamed, Hamatan; Agossou, Gadedjisso-Tossou; Segnon, Alcade C.; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A key challenge frequently mentioned by NMHSs limiting the operationalization the NextGen approach to seasonal climate forecasting systems, especially the use the PyCPT tool was the lack of consideration of hydrologic parameters. To address this challenge. AGRHYMET has adapted the PyCPT tool for seasonal hydrological forecasting. The adapted version of PyCPT has been illustrated and tested for seasonal hydrological forecasting for the 2023 rainy season, with satisfactory results. Future development needs to integrate additional features such as multi-model ensemble and flexible forecasts.